Issues and challenges of forests protecting in Sahel countries (Eurasian Journal of Ecology, 2022)
This article considers the main problems contributing to the reduction of forest resources in six Sahelian countries (Burkina Faso, Mali, Mauritania, Niger, Senegal and Chad) that threaten the achievement of their goals of regional stability and socio-economic development. The study finds its interest in the fact that it will make it possible to determine the climatic, energy and security constraints in the preservation of forest species in the Sahel. The methodology was based on carrying out documentary collections and analysis, cartographic analyzes, data processing and analysis. The study revealed that the issues and challenges of protecting forest areas are classified into three categories: climate change, energy issue due to the absence of new and renewable energies, poor coverage of electricity networks, high dependence of Sahelian communities on biomass and conflicts in the Sahel.  It is estimated that today more than 65 million people in this region do not have access to electricity, and 90 million still depend on the traditional use of biomass for cooking food. Considering these constraints will make it possible to find solutions to the evils of the Sahel through joint action between States, States and their partners and with communities.Key words: deforestation, Sahel, protection, threats, drought, charcoal production, energy consumption.